2020
DOI: 10.1002/mc.23205
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between cancer associated fibroblasts and immune cells in the context of radiation therapy

Abstract: Fibroblasts are a key component of the tumor microenvironment (TME) that can serve as a scaffold for tumor cell migration and augment the tumor's ability to withstand harsh conditions. When activated by external or endogenous stimuli, normal fibroblasts become cancer associated fibroblasts (CAFs), a heterogeneous group of stromal cells in the tumor that are phenotypically and epigenetically different from normal fibroblasts. Dynamic crosstalk between cancer cells, immune cells, and CAFs through chemokines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 146 publications
(387 reference statements)
1
25
0
Order By: Relevance
“…In general, our data suggest that spheroids generated after sequential seeding of fibroblasts in 1:3 ratio to the already formed MCF-7 aggregates (1000 cells/per well) were optimal for further investigation of fibrotic reactions. www.nature.com/scientificreports/ Fibrosis could be activated by external (e.g., RT) or endogenous (growth factors/cytokines) stimuli 37 . The common feature of the majority of fibrotic tissues is the overexpression of TGF-β, the most potent profibrotic cytokine 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In general, our data suggest that spheroids generated after sequential seeding of fibroblasts in 1:3 ratio to the already formed MCF-7 aggregates (1000 cells/per well) were optimal for further investigation of fibrotic reactions. www.nature.com/scientificreports/ Fibrosis could be activated by external (e.g., RT) or endogenous (growth factors/cytokines) stimuli 37 . The common feature of the majority of fibrotic tissues is the overexpression of TGF-β, the most potent profibrotic cytokine 27 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, with regard to the omental tumor microenvironment, omental fibroblasts are trans-differentiated from adipose-derived mesenchymal stem cells by ovarian cancer-derived exosomes and are associated with transforming growth factor beta (TGF-β) signaling secreted by both cancer cells and stromal cells [19,20]. TGF-β contributes to recruiting stromal cell types characterized by CAFs, inducing ECM production and downregulating the expression of ECM-associated protease [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies however have also suggested that CAFs provide the tumors with a pro-cancerous microenvironment and can serve as the leading structures for cancer progression [27,28]. These lowuptake lesions surrounding the tumor might therefore be precancerous, so far overlooked by radiation oncologists, thus requiring targeted radiation [29]. This hypothesis first requires validation through the gold standard of histopathological correlation in future studies.…”
Section: Discussionmentioning
confidence: 99%